Manipulation of the balance between Th2 and Th2/1 hybrid cells affects parasite nematode fitness in mice. Issue 12 (24th October 2018) - Affinass, Nicole; Zhang, Hongwei; Löhning, Max; Hartmann, Susanne; Rausch, Sebastian
Abstract: T‐helper type 2 (Th2) responses are central to the control of helminth infections, but sensitive to opposing cytokine signals favoring Th1 priming. We previously reported on GATA‐3 + T‐bet + Th2/1 hybrid cell differentiation in helminth mono‐infections, resulting in a substantial proportion of cells coproducing IFN‐γ next to Th2 cytokines. Here, we demonstrate Th2/1 cells as the major source of parasite‐specific IFN‐γ production in acute and chronic infections with the enteric nematode Heligmosomoides polygyrus . Th2/1 cells differentiated from naive precursors and accumulated in spleen and intestine of infected mice, resulting in increased systemic and mucosal IFN‐γ production. IFN‐γ supplementation early during infection supported Th2/1 differentiation, associated with elevated parasite fecundity and the maintenance of high worm burdens in the chronic stage of infection, whereas mice lacking IFN‐γ signals generated poor Th2/1 responses and restricted parasite fecundity more efficiently. These findings suggest that Th2/1 hybrid responses take part in immune regulation during helminth infection and restrain effective anti‐helminth immunity. Abstract : Intestinal nematode infection leads to the differentiation of Th2 and Th2/1 hybrid cells. Hybrids are most prominent in the spleen and accumulate with Th2 cells in the infected gut. IFN‐γ activity during the priming phase supports Th2/1 generation and results in increased susceptibility, evident as high worm burdens and fecundity.